An unusual finding in a 57-year-old woman with new onset hypertension and a diastolic murmur. Issue 21 (13th July 2016) - Tarkin, Jason M; Rudd, James H F; Jayne, David R; Rusk, Rosemary A; Gopalan, Deepa
Abstract : Clinical introduction: A 57-year-old woman presented to our clinic with breathlessness brought on while walking uphill. She had been recently diagnosed with systemic hypertension. There was no known family history of cardiac disease, or prior smoking habit. On examination, pulse was 73 bpm and blood pressure 155/73 mm Hg, which was asymmetrical in her arms. Auscultation revealed a readily audible early diastolic murmur in the aortic area and bilateral subclavian bruits. ECG showed sinus rhythm with no abnormality. Transthoracic echocardiography demonstrated mild-to-moderate aortic regurgitation, and normal left ventricular size and function. The ascending aorta was mildly dilated (41 mm), with para-aortic thickening noted. Owing to the abnormal appearance of the aortic wall, cardiac MRI, and subsequently 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET) scan was performed (figure 1 ). Question: Which complication of the underlying disease is evident in figure 1, panel C? Aortic aneurysm Aortic dissection Aortic thrombus Coronary artery aneurysm Coronary sinus fistula